Illustrated stories from Shakespeare - Shakespeare, William (Usborne London, 2010)
"This is a wonderful collection of six retellings of William Shakespeare's best-loved plays - a perfect mix of comedy, tragedy, magic and romance, retold for younger readers. It is full of colourful illustrations from the Usborne Young Reading Programme. It contains the plays "A Midummer Night's Dream", "Hamlet", "Macbeth", "Romeo and Juliet", "The Tempest", and "Twelfth Night". It also includes a section at the back on the life and times of Shakespeare."--Publisher description